In water multicomponent synthesis of low-molecular-mass 4,7-dihydrotetrazolo[1,5-a]pyrimidines - Tkachenko, Irina G.; Komykhov, Sergey A.; Musatov, Vladimir I.; Shishkina, Svitlana V.; Dyakonenko, Viktoriya V.; Shvets, Vladimir N.; Diachkov, Mikhail V.; Chebanov, Valentyn A.; Desenko, Sergey M. (Beilstein Journal of Organic Chemistry, 2019)
The three-component reaction of 5-aminotetrazole with aliphatic aldehydes (formaldehyde, acetaldehyde) and acetoacetic ester derivatives in water under microwave irradiation leads to the selective formation of 4,7-dihydrotetrazolo[1,5-a]pyrimidine derivatives. Under similar conditions using 4,4,4-trifluoroacetoacetic ester 5-hydroxy-4,5,6,7-tetrahydrotetrazolo[1,5-a]pyrimidines are obtained. The analogous reaction with acetylacetone requires scandium(III) triflate as catalyst. The antioxidant activity of selected compounds was assayed with 1,1-diphenyl-2-picrylhydrazyl.
Keywords: 5-aminotetrazole; antioxidant activity; 1,3-dicarbonyl compounds; multicomponent synthesis; tetrazolo[1,5-a]pyrimidines

(untitled) - Łakomska, I.; Fandzloch, M. (Coord. Chem. Rev., 2016)

(untitled) - Gein, V. L.; Mishunin, V. V.; Tsyplyakova, E. P.; Vinokurova, O. V.; Vakhrin, M. I. (Pharm. Chem. J., 2009)
Khim. Farm. Zh. 2009, 43, 12, 10-12.

(untitled) - Raju, C.; Madhaiyan, K.; Uma, R.; Sridhar, R.; Ramakrishna, S. (RSC Adv., 2012)

(untitled) - Dougherty, A. M.; Guo, H.; Westby, G.; Liu, Y.; Simsek, E.; Guo, J.-T.; Mehta, A.; Norton, P.; Gu, B.; Block, T.; Cuconati, A. (Antimicrob. Agents Chemother., 2007)

(untitled) - Orlov, V. D.; Desenko, S. M.; Pivnenko, N. S. (Chem. Heterocycl. Compd., 1988)
Khim. Geterotsikl. Soedin. 1988, 11, 1489-1493.

(untitled) - Desenko, S. M.; Gladkov, E. S.; Komykhov, S. A.; Shishkin, O. V.; Orlov, V. D. (Chem. Heterocycl. Compd., 2001)

(untitled) - Scheuermann, T. H.; Stroud, D.; Sleet, C. E.; Bayeh, L.; Shokri, C.; Wang, H.; Caldwell, C. G.; Longgood, J.; MacMillan, J. B.; Bruick, R. K.; Gardner, K. H.; Tambar, U. K. (J. Med. Chem., 2015)

(untitled) - Chebanov, V.; Sakhno, Y.; Desenko, S.; Shishkina, S.; Musatov, V.; Shishkin, O.; Knyazeva, I. (Synthesis, 2005)

(untitled) - Pryadeina, M. V.; Burgart, Y. V.; Saloutin, V. I.; Kodess, M. I.; Ulomskii, E. N.; Rusinov, V. L. (Russ. J. Org. Chem., 2004)

Int. Patent Appl. - Abelman, M.; Jiang, R.; Zablocki, J. (Optionally condensed dihydropyridine, dihydropyrimidine and dihydropyrane derivatives acting as late sodium channel blockers, 2009)

(untitled) - Kour, P.; Singh, V. P.; Khajuria, B.; Singh, T.; Kumar, A. (Tetrahedron Lett., 2017)

(untitled) - Maleki, A.; Ravaghi, P.; Aghaei, M.; Movahed, H. (Res. Chem. Intermed., 2017)

Azaheterocycles Based on α,β-Unsaturated Carbonyls - Chebanov, V. A.; Desenko, S. M.; Gurley, T. W. (Six-Membered Azaheterocycles Based on 1,3-Binucleophiles, 2008)

(untitled) - Wang, X.-C.; Wei, Y.; Da, Y.-X.; Zhang, Z.; Quan, Z.-J. (Heterocycles, 2011)

(untitled) - Ghorbani-Vaghei, R.; Toghraei-Semiromi, Z.; Amiri, M.; Karimi-Nami, R. (Mol. Diversity, 2013)

(untitled) - Gein, V. L.; Vladimirov, I. N.; Fedorova, O. V.; Kurbatova, A. A.; Nosova, N. V.; Krylova, I. V.; Vakhrin, M. I. (Russ. J. Org. Chem., 2010)

(untitled) - Yao, C.; Lei, S.; Wang, C.; Yu, C.; Tu, S. (J. Heterocycl. Chem., 2008)

(untitled) - Zeng, L.-Y.; Cai, C. (J. Comb. Chem., 2010)

(untitled) - Fedorova, O. V.; Zhidovinova, M. S.; Rusinov, G. L.; Ovchinnikova, I. G. (Russ. Chem. Bull., 2003)

(untitled) - Kolosov, M. A.; Shvets, E. H.; Manuenkov, D. A.; Kulyk, O. G.; Mazepa, A. V.; Orlov, V. D. (Synth. Commun., 2019)

Green Chemistry: Theory and Practice - Anastas, P. T.; Warner, J. C. (Oxford University Press, 1998)

Handbook of Green Chemistry - Odell, L. R.; Larhed, M. (Microwave‐Accelerated Homogeneous Catalysis in Water, 2009)

(untitled) - Dallinger, D.; Kappe, C. O. (Chem. Rev., 2007)

(untitled) - Wu, X.; Larhed, M. (Org. Lett., 2005)

(untitled) - Leeson, P. (Nature, 2012)

(untitled) - Komykhov, S. A.; Tkachenko, I. G.; Musatov, V. I.; Diachkov, M. V.; Chebanov, V. A.; Desenko, S. M. (ARKIVOC, 2016)

(untitled) - Tkachenko, I. G.; Komykhov, S. A.; Gladkov, E. S.; Musatov, V. I.; Chebanov, V. A.; Desenko, S. M. (Chem. Heterocycl. Compd., 2019)
Khim. Geterotsikl. Soedin. 2019, 55, 392-396.

(untitled) - Tkachenko, I. G.; Komykhov, S. A.; Musatov, V. I.; Chebanov, V. A.; Desenko, S. M. (Fr.-Ukr. J. Chem., 2019)

(untitled) - Desenko, S. M.; Gladkov, E. S.; Nenaidenko, V. G.; Shishkin, O. V.; Shishkina, S. V. (Chem. Heterocycl. Compd., 2004)
Khim. Geterotsikl. Soedin. 2004, 71-76.

(untitled) - Blois, M. S. (Nature, 1958)

(untitled) - Li, B.; Pratt, D. A. (Free Radical Biol. Med., 2015)

(untitled) - Kaur, I.; Geetha, T. (Mini-Rev. Med. Chem., 2006)

(untitled) - Sherma, J. (J. AOAC Int., 2018)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. C: Struct. Chem., 2015)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Adv., 2015)